Persistent Persister Misperceptions - Kim, Jun-Seob; Wood, Thomas K. (Frontiers in Microbiology, 2016)
ABSTRACT Persister cells survive antibiotic treatment due to their lack of metabolism, rather than through genetic change, as shown via four seminal experiments conducted by the discoverers of the phenotype (Hobby et al., 1942; Bigger, 1944). Unfortunately, over seven decades of persister cell research, the literature has been populated by misperceptions that do not withstand scrutiny. This opinion piece examines some of those misunderstandings in the literature with the hope that by shining some light on these inaccuracies, the field may be advanced and subsequent manuscripts may be reviewed more critically.